(untitled) (Computer-Assisted Language Comparison in Practice: Tutorials on Computational Approaches to the History and Diversity of Languages, 2023)
Colexifications have enjoyed a considerable amount of popularity in the recent years. However, there are still many semantic domains, where not much research on colexification patterns has been carried out so far. Here we show, how the recently published Lexibank repository can be queried to yield colexification data on taste colexifications which can in turn be easily plotted on geographic maps.